Clinical mastitis perceptions of Kansas dairy producers - J.R. Roberson (Kansas Agricultural Experiment Station Research Reports, 2003)
Mastitis is considered the most costly disease in the U.S. dairy industry. Treatment of clinical mastitis is the major reason for antibiotic contamination of products on U.S. dairy farms. A survey of 183 dairy producers was conducted to determine their perceptions regarding clinical mastitis treatments and what constituted their treatment regimens. Results indicated that 33% of dairy producers used a coliform vaccine, 10% used a Staphylococcus aureus vaccine, and 38% did no prestripping before milking cows. Obtaining a clinical cure (restoration of normal milk) was considered the most important aspect of mastitis treatment success (110/183; 60%) compared to bacteriological cure (absence of bacterial pathogen), somatic cell count cure (cells count back to near normal concentrations), milk production (back to near pre-mastitis levels), and udder firmness (back to near normal firmness). Average treatment success for mastitis reported by the 183 producers was 70%, with a range of 10 to 100%. Seventy-three (92%) producers listed off-feed as a good measure of the severity of clinical mastitis, followed closely by general appearance (91%). Appearance of udder and milk, droopy ears, appearance of the eyes, and low milk production were other popular methods used to determine the severity of clinical mastitis. Dairy producers believed that 5.3 days (range of 1 to 45 days) passed between first recognition of a clinical case until normal milk was restored. Only 34% of producers utilized rectal temperatures as a diagnostic tool for mastitis. Many treatments used were extra-label and some were potentially illegal. However, the results presented demonstrate a wide diversity of products used and a general lack of consensus of what is considered efficacious mastitis treatment. In addition, drug dosages and duration of therapy varied considerably. Greater education on proper dosages, durations, and potential efficacy of treatments should be beneficial. A clear need exists for conducting efficacy studies to help establish necessary and justified treatments for clinical mastitis.; Dairy Day, 2003, Kansas State University, Manhattan, KS, 2003;
Keywords: Dairy Day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-129-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 919; Dairy; Milking routines; Mastitis survey; Mastitis therapies